Both N-Terminal and C-Terminal Histidine Residues of the Prion Protein Are Essential for Copper Coordination and Neuroprotective Self-Regulation. Issue 16 (24th July 2020) - Schilling, Kevin M.; Tao, Lizhi; Wu, Bei; Kiblen, Joseph T.M.; Ubilla-Rodriguez, Natalia C.; Pushie, M. Jake; Britt, R. David; Roseman, Graham P.; Harris, David A.; Millhauser, Glenn L.
Abstract: The cellular prion protein (PrP C ) comprises two domains: a globular C-terminal domain and an unstructured N-terminal domain. Recently, copper has been observed to drive tertiary contact in PrP C, inducing a neuroprotective cis interaction that structurally links the protein's two domains. The location of this interaction on the C terminus overlaps with the sites of human pathogenic mutations and toxic antibody docking. Combined with recent evidence that the N terminus is a toxic effector regulated by the C terminus, there is an emerging consensus that this cis interaction serves a protective role, and that the disruption of this interaction by misfolded PrP oligomers may be a cause of toxicity in prion disease. We demonstrate here that two highly conserved histidines in the C-terminal domain of PrP C are essential for the protein's cis interaction, which helps to protect against neurotoxicity carried out by its N terminus. We show that simultaneous mutation of these histidines drastically weakens the cis interaction and enhances spontaneous cationic currents in cultured cells, the first C-terminal mutant to do so. Whereas previous studies suggested that Cu 2+ coordination was localized solely to the protein's N-terminal domain, we find that both domains contribute equatorially coordinated histidine residue side-chains, resulting in a novel bridging interaction. We also find that extra N-terminal histidines in pathological familial mutations involving octarepeat expansions inhibit this interaction by sequestering copper from the C terminus. Our findings further establish a structural basis for PrP C 's C-terminal regulation of its otherwise toxic N terminus. Graphical abstract: Unlabelled Image Highlights: The two domains of the cellular prion protein are tethered together by a copper ion. This tethering is the basis of the protein's neuroprotective cis interaction . Disruption of this interaction explains the toxicity of prion diseases. Disruption may explain prion protein mediated toxicity in Alzheimer's disease